Arranjo espacial de plantas na cultura do pinhão manso em Selvíria (MS) - Daniel, Henrique [UNESP] (2013)
The new orientation of energy agriculture is to produce raw materials for biodiesel, and one of the alternatives, Jatropha grains. To obtain information about the culture, developed this study to evaluate the vegetative growth, yield of Jatropha grains and Total Operating Cost in the first year after planting, depending on spatial arrangements between plants. The experiment was conducted in the experimental area of UNESP - Ilha Solteira Campus, located in Selvíria County, Mato Grosso do Sul State, Brazil,in the period from 04/09/2010 to 07/27/2011. We used a randomized block design, with 17 treatments and 4 replications. The spacing between rows and between plants used were, respectively: 2.0x1.0, 2.0x1.5, 2.0x2.0, 3.0x1.0, 3.0x1.5, 3.0x2.0, 3.0x3.0, 4.0x1.0, 4.0x1.5, 4.0x2.0, 4.0x3.0, 4.0x4.0, 5.0x1.0, 5.0x1.5, 5.0x2.0, 5.0x3.0 and 5.0x4.0 m. It was done 7 evaluations on plants phenology of fruit and 3 harvests. Jatropha plants had an average height of 2.26 m, stem diameter of 101 mm, 6 branches per plant, six inflorescences, four clusters, the average canopy diameter of 2.06 m and the avarage closure of street was 60%. Treatments did not influence the relationship peel/fruit that average was 31.3 wt%. The most dense spacing, 2.0x1.0, 3.0x1.0 and 3.0x1.5 m, were the most productive, with yield of 821, 887 and 1.027 kg ha -1 , respectively. The Total Operating Cost in the crop establishment, spaced 3,0x1,0 m was R$ 6,751.34 ha -1 and spacing of 4.0x4.0 m was R$ 3,154.43 ha -1 , while driving in 1 st year was R$ 4,945.19 ha -1 and R$ 4,097.17 ha -1 , respectively